A high‐quality reference genome sequence of Salvia miltiorrhiza provides insights into tanshinone synthesis in its red rhizomes. Issue 3 (17th September 2020) - Song, Zhenqiao; Lin, Caicai; Xing, Piyi; Fen, Yuanyuan; Jin, Hua; Zhou, Changhao; Gu, Yong Q.; Wang, Jianhua; Li, Xingfeng
Abstract: Salvia miltiorrhiza Bunge, also known as red sage or Danshen, is an important traditional Chinese medicine (TCM) that has been used for thousands of years to treat cardiovascular and other diseases. It is also considered an important model TCM plant. Here, a high‐quality reference genome of S. miltiorrhiza was generated by combining PacBio long‐read sequencing and chromatin interaction mapping (Hi‐C) technologies, resulting in the chromosome‐scale assembly of a 594.75‐Mb genome sequence with a contig N50 of 2.70 Mb. This assembly shows the highest level of continuity for a Danshen genome generated thus far. The S. miltiorrhiza genome contained 32, 483 protein‐coding genes, with a repetitive DNA content of approximately 64.84%. The high percentage of young LTRs suggests that multiple TE transposition bursts occurred recently in S. miltiorrhiza . Genes unique to secondary metabolism pathways were expanded in the S. miltiorrhiza genome. A new CYP450 gene cluster was identified in the phloem of red roots where active components were synthesized. This reference genome sequence will facilitate future studies aimed at the elucidation of the secondary metabolism synthesis pathway and the genetic improvement of S. miltiorrhiza .